The Impacts of the Fraud Diamond Dimension, Religiosity, and Misuse of Information Technology on Student Academic Dishonesty - Netty Herawaty; Masbirorotni Masbirorotni (Universitas Jambi, Indonesia, 2022)
This research aimed to find out and analyze how the dimensions of fraud diamond, religiosity, and misuse of information technology affect student academic dishonesty in the COVID-19 era. This research used primary data by distributing questionnaires. The population of this research was active students in the faculty of economics and business, in one public university in Jambi. The sampling of this research used the Slovin formula for a minimum of 98 respondents. The method of data analysis was done by using the multiple regression. The research results showed that the fraud diamond dimension affected academic dishonesty, however, religiosity did not affect academic dishonesty, while misuse of information technology affected academic dishonesty.